2022
DOI: 10.3390/jcm11195885
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Chair Positioning Session on Awake Non-Intubated COVID-19 Pneumonia Patients: A Multicenter, Observational, and Pilot Study Using Lung Ultrasound

Abstract: Background: LUS is a validated tool for the management of COVID-19 pneumonia. Chair positioning (CP) may have beneficial effects on oxygenation and lung aeration, and may be an easier alternative to PP. This study assessed the effects of a CP session on oxygenation and lung aeration (LA) changes in non-intubated COVID-19 patients. Methods: A retrospective multicenter study was conducted in an ICU. We analyzed data from LUS exams and SpO2:FiO2 performed before/after a CP session in non-intubated COVID-19 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…This kind of correlation was also observed for intubated patients [44]. So, LUS has also been used to evaluate responses to therapeutic acts such as non-invasive ventilation [45]; in a prospective observational study, it was observed that LUS score >12 was predictive of NIV failure [46] and it was also employed for prone positioning trial response [46,47].…”
Section: Prognostic Stratification and Monitoringmentioning
confidence: 83%
“…This kind of correlation was also observed for intubated patients [44]. So, LUS has also been used to evaluate responses to therapeutic acts such as non-invasive ventilation [45]; in a prospective observational study, it was observed that LUS score >12 was predictive of NIV failure [46] and it was also employed for prone positioning trial response [46,47].…”
Section: Prognostic Stratification and Monitoringmentioning
confidence: 83%